Discovery of a dual active galactic nucleus with ∼8 kpc separation. (12th May 2017) - Ellison, Sara L.; Secrest, Nathan J.; Mendel, J. Trevor; Satyapal, Shobita; Simard, Luc
Abstract: Targeted searches for dual active galactic nuclei (AGNs), with separations 1–10 kpc, have yielded relatively few successes. A recent pilot survey by Satyapal et al. has demonstrated that mid-infrared (mid-IR) pre-selection has the potential to significantly improve the success rate for dual AGN confirmation in late stage galaxy mergers. In this Letter, we combine mid-IR selection with spatially resolved optical AGN diagnostics from the Mapping Nearby Galaxies at Apache Point Observatory survey to identify a candidate dual AGN in the late stage major galaxy merger SDSS J140737.17+442856.2 at z  = 0.143. The nature of the dual AGN is confirmed with Chandra X-ray observations that identify two hard X-ray point sources with intrinsic (corrected for absorption) 2–10 keV luminosities of 4 × 10 41 and 3.5 × 10 43 erg s −1 separated by 8.3 kpc. The neutral hydrogen absorption (∼10 22 cm −2 ) towards the two AGNs is lower than in duals selected solely on their mid-IR colours, indicating that strategies that combine optical and mid-IR diagnostics may complement techniques that identify the highly obscured dual phase, such as at high X-ray energies or mid-IR only.